PEMANFAATAN MEDIA YOUTUBE DALAM PEMBELAJARAN PAI BERBASIS DARING DI MASA PANDEMI COVID-19 UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VIII 7 SMP NEGERI 11 TANGGERANG SELATAN TAHUN 2021 - Halimatus Sadiyah (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
This study aims to determine the use of Youtube media on student learning outcomes in PAI learning in class VIII 7 students at SMP Negeri 11 Tangerang Selatan City in 2021. The research objectives in this study are; Describe the process of using Youtube media to improve student learning outcomes in online-based PAI learning for class VIII 7 SMP Negeri 11 Tangerang Selatan; Describes the increase in student learning outcomes for class VIII 7 SMP Negeri 11 Tangerang Selatan after using Youtube media in online-based PAI learning. This research uses classroom action research method, the activities are carried out in two cycles with stages; planning, implementation, results and reflection. The data collection technique used a test assessment rubric. Data analysis in this study is qualitative and quantitative. The increase in student learning outcomes is shown in the comparative average value of student learning outcomes in pre-cycle, cycle I, and cycle II with a KKM score of 75. In the initial conditions students get an average score of 61.34 with a percentage of 26.66% of participants students who complete, then in the first cycle students get an average score of 72.34 with a percentage of 54% of students who complete and in the second cycle students get an average score of 80.67 with a percentage of 100% of students who complete.